Menumbuhkan Jiwa Kewirausahaan Sejak Dini Pada Siswa-Siswi Kelas 6 SD Negeri 75 Kota Bengkulu - Yustanti, Nirta Vera; Rafles, Fadhlu Rohman Dian (Jurnal Kewirausahaan dan Bisnis, 2023)
Currently, students or the community are required to be able to innovate in an increasingly modern era, one of which is the community service team of Dehasen University Bengkulu collaborating with State Elementary School 75 Bengkulu City in fostering an entrepreneurial spirit from an early age. This community service is aimed at students of State Elementary School 75 Bengkulu City which aims to instill entrepreneurial insights, as well as foster an entrepreneurial spirit from an early age. Having an entrepreneurial spirit is an important point for students in the future. In addition, from this activity, it is hoped that students can help the family economy and can also take advantage of their spare time to do positive activities by way of entrepreneurship and minimize juvenile delinquency. This community service socialization uses the method of explaining to students the importance of entrepreneurial knowledge and the importance of entrepreneurship and conducting questions and answers to students about the entrepreneurial material that has been delivered.